A Analysis of Islamic Banks in Indonesia and Malaysia Using CAMEL - Pipin Lestari; Widhian Hardiyanti (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2020)
Indonesia is a country with the largest Muslim population in ASEAN, but in Islamic banking Indonesia is still lagging behind Malaysia. This study compares the financial performance of Islamic banking in both countries with the CAMEL method. There are five aspects to the CAMEL approach, namely Capital Adequacy (CAR), Asset Quality (NPF), Management Quality (NPM), Earnings (ROA, BOPO), and Liquidity (FDR). The analytical tool used is a different t-test to find out whether there is a difference or not between the financial performance of Indonesian and Malaysian sharia. From the results of data analysis with the Independent t-test three variables namely (NPF, NPM, BOPO) showed significant differences, while the variables (CAR, ROA, and FDR) there were no significant differences between Indonesian and Malaysian banks.